2023
DOI: 10.2174/011871529x278907231120053559
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Drug Targets and Combination Therapy for the Clinical Management of Hypertension

Pradeep Kumar Niranjan,
Shiv Bahadur

Abstract: Raised blood pressure is the most common complication worldwide that may lead to atherosclerosis and ischemic heart disease. Unhealthy lifestyles, smoking, alcohol consumption, junk food, and genetic disorders are some of the causes of hypertension. To treat this condition, numerous antihypertensive medications are available, either alone or in combination, that work via various mechanisms of action. Combinational therapy provides a certain advantage over monotherapy in the sense that it acts in multi mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 120 publications
0
1
0
Order By: Relevance
“…This is complicated by the fact that high blood pressure may show no symptoms even for many years, thus posing a significant challenge for its management [ 36 ]. Moreover, it has been demonstrated that monotherapy is often not sufficient to lower blood pressure in hypertensive patients [ 37 ]. Egan and colleagues reported that administering combination therapy, which involves the use of multiple antihypertensives, could be an alternative approach to managing hypertension because it induces better cardiovascular outcomes than monotherapy [ 38 ].…”
Section: Hypertension and Strokementioning
confidence: 99%
“…This is complicated by the fact that high blood pressure may show no symptoms even for many years, thus posing a significant challenge for its management [ 36 ]. Moreover, it has been demonstrated that monotherapy is often not sufficient to lower blood pressure in hypertensive patients [ 37 ]. Egan and colleagues reported that administering combination therapy, which involves the use of multiple antihypertensives, could be an alternative approach to managing hypertension because it induces better cardiovascular outcomes than monotherapy [ 38 ].…”
Section: Hypertension and Strokementioning
confidence: 99%